Pengaruh Personalisasi Artificial Intelligence dan Pengalaman Pelanggan terhadap Loyalitas Pelanggan: Studi pada Pengguna E-Commerce Shopee di Kabupaten Lamongan - Mohammad Bastian Dwiki Rahmat; Darianto Darianto; Amanatul Khoiriyah (Universitas Nusantara PGRI Kediri, 2026)
The growth of digital commerce in Indonesia continues to increase in line with shifting consumer shopping patterns that are becoming increasingly dependent on personalized online interactions. This study examines the influence of Artificial Intelligence personalization and customer experience on customer loyalty toward the Shopee platform in Lamongan Regency. A quantitative approach was applied using purposive sampling, involving 100 active users aged 18 - 40 years who had conducted multiple transactions within the past three months. The research employed structured questionnaires as the primary data-gathering instrument, and the resulting responses were examined through multiple linear regression using SPSS version 27. The analysis reveals that AI-driven personalization, together with customer experience, contributes positively to enhancing customer loyalty. These variables also reinforce each other when combined, suggesting that relevant services and consistent user experiences can enhance customers’ tendency to continue using the Shopee e-commerce platform. This study emphasizes the importance of integrating Artificial Intelligence systems with customer experience design that prioritizes convenience to foster long-term relationships with digital consumers.